The Islamic Intellectual Intelligence as a Social Class - Apriandi, Budi; Thaheransyah; Kamal, Tamrin; SA, Saifullah; Asmaret, Desi; Julhadi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Islamic intelligence in Indonesia has experienced ups and downs, both politically and intellectually. The transformation of Indonesian Islamic Information Services, which were initially marginalized by intellectuals, politics, and bureaucracy in Indonesia, to a central position is one example of the long journey of Islamic Information Services in Indonesia. The emergence of Indonesian intellectuals at the end of the 19th century and the first two decades of the 20th century manifested in several names that continued to evolve, from the birth of figures to the emergence of Bangsawan Oesoel and Kaoem Muda. Kaoem, educated youth, or john. The emergence of the Secret Service was influenced by the ethical revolution in the Dutch East Indies due to the liberal economic crisis in the Dutch East Indies. Additionally, this period was marked by the entry of modernist Islamic reformism, which sought to balance the Western secularism trend. The 20th century witnessed various struggles for recognition and political authority. From the late 20th century to the early 21st century, many changes occurred in the economic and political systems, with successive government changes. This period was also marked by an economic crisis, signaling the beginning of the second economic era after the ethical reforms in the Dutch East Indies. Therefore, it can be said that active participation and power struggles took place among Indonesian Islamic intellectuals. Thus, the formation of Indonesia’s political and bureaucratic elite cannot always be separated from the development and changes in the map of Indonesia’s Islamic intelligence institutions. In fact, they have been at the core of Indonesia’s political elite, from the implementation of Dutch ethical policies to the post-reform regimes.